Microdureza de los sistemas de instrumentación mecanizados E-FlexBlue®, E-FlexOne® y E-Flex Edge® - Calderón López, Juan (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Lacking Standardization Standards in the manufacture of mechanized files, each manufacturer provides elements that differ totally or partially from the rest, the Microhardness of the instruments being no exception, which is why knowing this information about the E-Flex Blue instruments®, E-Flex One® and E-Flex Edge® is important in seeking to ensure that the results of endodontic treatments are increasingly predictable. AIM. Evaluate the Microhardness results of the instruments using Vickers Microhardness Tester (HV). HYPOTHESIS. The Microhardness results between the instruments of the E-Flex Blue®, E-Flex One® and E-Flex Edge® Mechanized Systems using Vickers Microhardness Tester (HV). They will be different. METHODOLOGY. To be certain of the surface finish of the instruments and to be able to carry out the microhardness study, the sectioned files were observed under an optical microscope at 5X Zeiss® Axio Observer®, obtaining photomicrography of the active part, prior to the indentations by microhardness test. Vickers. The determination of hardness was carried out in accordance with the ASTM E-92 standard, using a Vickers Autovick® Mitutoyo HM-200 indenter with a load of 200 grams and a residence time of 15 seconds at 5 sampling points per instrument. The test instruments were placed in the sample holder and must have a completely flat and clean surface. A conical diamond indenter printed the sample with an angle α = 136° between their surfaces. After removing the load, the pyramid remained under the load P of 200 grams and a residence time of 15 seconds at 5 sampling points per instrument, using a microscope, the two diagonals of the left footprint were measured.

Al carecer de Normas de Estandarización en la fabricación de las limas mecanizadas, cada fabricante proporciona elementos que difieren total o parcialmente del resto, la Microdureza de los instrumentos no siendo la excepción, es por eso que conocer esta información de los instrumentos E-Flex Blue®, E-Flex One® y E-Flex Edge® es importante buscando obtener que los resultados de los tratamientos endodónticos sean cada vez más predecibles. OBJETIVO. Evaluar los resultados de la Microdureza de los instrumentos utilizando Microdurómetro de Vickers (HV). HIPÓTESIS. Los resultados de la Microdureza entre los instrumentos de los Sistemas Mecanizados E-Flex Blue®, E-Flex One® y E-Flex Edge® utilizando Microdurómetro de Vickers (HV). serán diferentes. METODOLOGIA. Para tener la certeza del acabado superficial de los instrumentos y poder realizar el estudio de microdureza, las limas seccionadas se observaron en microscopio óptico a 5X Zeiss® Axio Observer®, obteniendo fotomicrografía de la parte activa, previo a las identaciones por prueba de microdureza de Vickers. La determinación de la dureza se realizó de acuerdo con la norma ASTM E-92, utilizando un indentador Vickers Autovick® Mitutoyo HM-200 con una carga de 200 gramos y un tiempo de permanencia de 15 segundos en 5 puntos de muestreo por instrumento. Los instrumentos de prueba se colocaron en el porta muestras debiendo tener una superficie completamente plana y limpia. Un indentador de diamante cónico imprimió la muestra con un ángulo α = 136° entre sus superficies. Después de retirar la carga, la pirámide permaneció bajo la carga P de 200 gramos y un tiempo de permanencia de 15 segundos en 5 puntos de muestreo por instrumento, usando un microscopio, se midió las dos diagonales de la huella izquierda.
Facultad de Odontología. Especialidad en Endodoncia
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16607; info:eu-repo/classification/cti/3; FO-E-2023-1041; Microdureza; Vickers; E-FlexBlue